Elementos traza en peces comerciales de Argentina - Llamazares Vegh, S. (2021)
Argentina is a strategic food-producing country worldwide. Among the foods produced, animal protein from fishing and aquaculture production stands out. In 2019 approximately more than 463,000 tonnes (t) of marine fish were caught, 30,000 t of freshwater fish, and 3,000 t were produced by aquaculture; and around 90% of all these products are exported. The trace elements present in fishery products can lead to significant economic losses due to the rejection of these products in external and internal markets and a potential health impact if their consumption is higher than the values proposed in the Argentine Food Code, and international regulations. However, in Argentina, studies on this subject are limited. This article presents a review of the studies related to the presence of trace elements regulated by the CAA (eg As, Cd, Cr, Cu, Hg, Pb and Zn) in muscle of the main species of coastal-marine and freshwater commercial fish of capture fisheries from Argentina. Also, the main results of trace elements in water and sediments in the last 20 years of the regions that concentrate capture fisheries are summarized. Existing information gaps are identified and different scientific-technical lines to be followed are discussed and proposed in order to contribute to the competent authorities in decision-making.